BREAKING DOWN BARRIERS: EVALUATING A MARIE CURIE HOSPICE PROJECT AIMED AT IMPROVING ACCESS TO PALLIATIVE CARE BY MINORITY ETHNIC GROUPS. Issue 1 (1st March 2013) - Baillie, J; Harrop, E; Byrne, A; Stephens, K; Nelson, A
Abstract : Introduction: Government policy within the UK (UK) asserts that all individuals should have access to high quality palliative care. However, there is a growing body of evidence that both internationally and within the UK, individuals from minority ethnic groups are underrepresented in both accessing and using palliative care services (PCS). A hospice within a major city in the UK is attempting to increase minority groups' utilisation of PCS by employing a key worker to engage with local communities. This study aims to inform and evaluate the development and impacts of this project. Aims and Methods: Semi-structured interviews are being undertaken with community members of minority ethnic community groups, community healthcare professionals and hospice staff, which will be repeated at 12 and 30 months. The key worker will also be interviewed at 6 monthly intervals. Ethnicity data collected by the hospice is also being analysed to identify whether there are changes to the uptake of palliative care over time. Results: Early data indicates that language and translation remains a concern for both healthcare professionals and members of minority ethnic communities. People from minority ethnic groups were unaware of the hospice services available, while healthcare professionals wanted additional education about the specific beliefs of people from different religious groups at the end of life. Ensuring that hospices have appropriate facilities to support religious needs is vital, especially for prayers. Conclusions: Implications will be identified for palliative care providers interested in finding ways to improve access to palliative care for minority ethnic groups.